GORĄCZKA u dzieci – reKOMendacje PostępowaniA w praktyce lekarza podStawowej opieki zdrowotnej – KOMPAS GORĄCZKA - Doniec, Zbigniew; Jackowska, Teresa; Sybilski, Adam; Woroń, Jarosław; Mastalerz-Migas, Agnieszka (Family Medicine & Primary Care Review, 2021)
In children, fever is a symptom of a wide spectrum of diseases, ranging from common self-limiting viral upper respiratory tract infections to serious life-threatening diseases. The aim of the diagnostic procedure is to identify the cause of fever, determine indications for outpatient treatment, plan the appropriate pharmacological therapy or reveal the need for hospitalisation. Paracetamol and ibuprofen are antipyretics recommended for symptomatic treatment of children; however, the medications should not be used in combination or alternately, except in specific clinical situations. The drugs may be applied to treat fever and topical reactions after vaccination, but not prophylactically in order to reduce the incidence of fever or local discomfort after vaccination. Both medications can be used in patients with asthma, with the exception of intolerant children. Children with confirmed or suspected COVID-19 may be treated with paracetamol and ibuprofen in accordance with clinical indications and dosage recommendations.